Pengelolaan Ruang Terbuka Hijau Oleh Dinas Lingkungan hidup Kabupaten Gowa - Putri, Nurfasani; Fatmawati, Fatmawati; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2024)
Environmental management is closely related to the welfare of society, with good and correct management and protection of the environment can realize the welfare of society in a country. This research aims to determine the of green open space management by the Gowa district environmental service. This research uses a qualitative descriptive method with data collection techniques using observation, interviews and documentation. The informants in this research were 3 people consisting of the Secretary of the Environmental Service, Head of the Waste Parks or Tahura Division, Functional Staff.The results of this research indicate that the of green open space management by the Gowa district environmental service is generally quite good but has not been implemented optimally in terms of aspects: (1) planning/implementation, planning/implementation of activities is not sufficient due to lack of facilities and infrastructure is still limited (2) organization, organization in this activity is quite good because there are many agencies involved in greening management (3) supervision, supervision in this activity is not good enough because plant resource officers are still quite low and become wrong a significant obstacle to green management.